Efficacy of insecticides against wheat thrips Haplothrips tritici Kurd. in winter wheat crops - Iu. Klechkovskyi; V. Klychko; G. Khorohorina (Карантин і захист рослин)
Goal. To develop an effective system of winter wheat protection against wheat thrips Haplothrips tritici Kurd. Determine the technical effectiveness of insecticides Karate Zeon 050 CS, SC (lambda-cyhalothrin, 50 g/l); Match 050 ES, CE (lufenuron, 50 g/l); Enjio 247 SC, CS (thiamethoxam, 141 g/l + lambda-cyhalothrin, 106 g/l); Talstar, 10% CE (bifenthrin, 100 g/l); Mospilan, VP (acetamiprid, 200 g/kg); Inazuma, VG, (acetamiprid, 100 g/kg + lambda-cyhalothrin, 30 g/kg) in the Southern Steppe of Ukraine.